School of German Language - S. V. Evteev (Vestnik MGIMO-Universiteta)
Department of German is one of the oldest language departments at MGIMO. Since its foundation in 1944 the military experienced teachers of the department, most of whom were native speakers, have begun to develop a unique method of teaching the German language, thereby revolutionize learning this foreign language. The first steps made under the supervision of the Department of Antonina V. Celica. The department refused to conventional time and is still used in universities such as the Moscow Linguistic University, separate teaching phonetics, grammar and vocabulary, which was due to the specific objectives set for the teaching staff: prepare for short term specialists in international relations, active Germanspeaking. The department can be proud of its graduates, many of whom continue his career in the walls of native high school. Many graduates have dedicated their lives to serving the State in the Ministry of Foreign Affairs.